Sedimentary facies and reservoir characteristics of limestone in Koh Formation, Sungai Relai, Aring, Kelantan - Muhammad Zarul Izat Azam (2016)
End product of this research is to uncover a scientiﬁc mystery; is there any reservoir rocks (oil and gas) are available in the study area: Koh Formation, Sungai Relai, Aring, Kelantan. The study area is located in Mukim Aring (in Gua Musang District of Kelantan) between the latitude of N 4°47'30.00" to N 4°50'15.00" and longitude E 102°10‘40.00" to E 102°13'25.00". It lies mainly on the Koh Fonnation and slightly on the Telong Formation and Nilam Marble. Only sedimentary rocks of the Koh Formation are analyzed in this study. Three major aims of this study are; (1) to produce a geological map (scales 1:25000) of the study area, (2) to detennine sedimentary facies of the Koh Formation and its depositional environment, and (3) to analyze the reservoir characteristics and diagenesis of selected sedimentary facies. Geological mapping is conducted throughout the study area to produce the geological map. Then, sedimentary facies presents in the study area are determined as well as its depositional enviromnent via facies analysis and depositional model. It is later followed by petrographic and petrophysical properties analysis to identify reservoir characteristics of the selected facies in the Koh Formation. Based on facies analysis performed, four distinctive sedimentary facies are determined; (l) Facies A: Intrasparite Allochemical Limestone, (2) Facies B: Laminated Sandstone, Siltstone and Shale, and (3) Facies C: Reddish Grey Argillaceous Limestone and Shale. In ancient time, Facies A was deposited at carbonate ramp environment, Facies B at subaqueous delta, and Facies C deposited at continental shelf, and formed the sedimentary rocks today in the study area. Limestone of Facies A is the only selected facies to carry out reservoir properties’ test. Porosity and permeability of the limestone was identiﬁed as extremely bad. This is due to the diagenetic processes; compaction and cementation that had reduced the porosity of the rock during the burial. Hence, limestone of the Koh Formation does not exhibit any potential to become a reservoir rock.